2020
DOI: 10.1155/2020/7172052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Efficacy of Traditional Chinese Medicine in Recovery Stage of Stroke: A Systematic Review and Meta-Analysis

Abstract: Background. We provide an updated meta-analysis with detailed information on a combination of TCM and routine treatment. Methods. Retrieve appropriate articles with no language restrictions on keywords until 8 July 2019 in an electronic database. All trajectories are screened according to certain criteria. The quality of certified research was also evaluated. We made a detailed record of the results of the measurement. Meta-analysis was carried out by using the Revman 5.3 software. Results. Sixty-seven RCTs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Prevention of stroke requires timely control of the primary disease, improvement of unhealthy lifestyles and habits, followed by initiation of secondary prevention therapy, which mainly includes blood pressure control, antipolymerization and lipid regulation plus plaque stabilization; moreover, combination of the three methods can reduce the risk of stroke. 80% incidence [ 21 , 22 ]. Chinese medicine emphasizes on stroke care: maintain emotional well-being and reduce adverse stimulation; keep the room sunny and ventilated; eat more light, digestible, high-quality protein-rich foods; carry out traditional Chinese medicine special care, such as cupping, acupuncture and traditional Chinese medicine fumigation; often observe the vital signs and state of consciousness of the patients in the acute stage, and pay attention to the nursing of the second bowel movement [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of stroke requires timely control of the primary disease, improvement of unhealthy lifestyles and habits, followed by initiation of secondary prevention therapy, which mainly includes blood pressure control, antipolymerization and lipid regulation plus plaque stabilization; moreover, combination of the three methods can reduce the risk of stroke. 80% incidence [ 21 , 22 ]. Chinese medicine emphasizes on stroke care: maintain emotional well-being and reduce adverse stimulation; keep the room sunny and ventilated; eat more light, digestible, high-quality protein-rich foods; carry out traditional Chinese medicine special care, such as cupping, acupuncture and traditional Chinese medicine fumigation; often observe the vital signs and state of consciousness of the patients in the acute stage, and pay attention to the nursing of the second bowel movement [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis study demonstrated that Paeoniae Rubra Radix (Chi Shao), Angelicae Sinensis Radix (Dang Gui), Astragali Radix (Huang Qi), Puerariae Lobatae Radix (Ge Gen), and Salviae Mihiorrhizae Radix et Rhizoma (Dan Shen) could relieve the symptoms of convalescent stroke patients, promote neurological function recovery, and improve the ADL effectively ( Zhang et al, 2020 ). Many Chinese herbs or herbal formulations (such as Salviae Mihiorrhizae Radix et Rhizoma (Dan Shen), Notoginseng Radix et Rhizoma (San Qi), Astragali Radix (Huang Qi), Bu Yang Huan Wu Tang, and Dang Gui Shao Yao San) have demonstrated significant pro-angiogenic and neuroprotective effects ( Seto et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Zhang (26) concluded that TCMs combined with routine treatment affect the blood lipid by regulating the contents of TC, TG, LDL, and HDL, and are beneficial to the rehabilitation of patients in the recovery period of apoplexy.…”
Section: Discussionmentioning
confidence: 99%